PENGARUH LATAR BELAKANG PENDIDIKAN, PENGETAHUAN AKUNTANSI PEMILIK, DAN UKURAN USAHA KECIL MENENGAH (UKM) TERHADAP PENERAPAN SAK-ETAP DI KOTA SEMARANG - Yogi Ari Prakoso; Andwiani Sinarasri; Fatmasari Sukesti (MAKSIMUM, 2017)
This research aims to prove evidence on the influence of owner’s educational background, owner’saccounting knowledge, and size of business towards the implementation of SAK ETAP on SMEs located inSemarang City used  quantitative method by using primary data. Used 83 samples with determination used theslovin formula. In this research used IBM SPSS for Windows 23 with three independent variables are owner’s educational background, owner’s accounting knowledge, and size of business and the implementation of SAKETAP as the dependent variable. The testing data used instrument test to consist of validity test and reliabilitytest, classic assumption test which consist of normality test, multikolinierity test, heteroskedastisity test, andautocorrelation, together with hypotesys test which covers f-test and t-test. The results show that the owner’s educational background do positive and not significantly effect on the implementation of SAK ETAP, owner’s accounting knowledge do positive and significantly effect on theimplementation of SAK ETAP, and size of business do positive and significantly effect on the implementationon the SAK ETAP partially, and taken tog ether simultaneously test do positive and significantly effect on theimplementation of SAK ETAP.